Transferência simultânea de calor e massa em secagem de grãos de cereais : uma abordagem por elementos de contorno - Vieira, William Gonçalves (1997)
Drying is an important process for grains conservation during their storage. In order to be done it in a suitable way it is necessary to know its mechanisms. These mechanisms are studied by laboratories experiments and follow a real drying situation and then simulating this mechanisms in computer. The computer studies, which is the scope of this work, simulate the physics of the phenomena by mathematical equations and the process is numerically simulated by the Boundary Elements Method. For this, it was done both mass and energy balance in a spherical body and it was obtained the equations of mass and heat diffusion. In the resulted equations, the expressions involving mass gradient in the thermical diffusion equations and humidity vaporization expression in the boundary condition, become coupled the model in a way that is different from others in literature. The choice of spherical shape is because the mathematical facilities and by the fact of several grains present spherical shape profile. Boundary Element Method is used in order to take numerical and computational advantages from the mathematical model. Furthermore, an uncoupled model was also solved, in order to compare results from two models. The suggested modeling was applied to one soybean grain, considering it as a spherical, porous and isotropic body with 3.5 mm radius. The integral equations obtained by applying the boundary element method to the problem with and without moisture coupling was solved by the collocation method, using quadratic discretization in domain, and linear interpolation in time. The moisture results, obtained numerically, have good agreement to analytical and available literature results. The temperature's results obtained by the model with mass coupled were similar to literature results and they differ from the results obtained by the uncoupled mass term model. It concludes that the coupled model is suitable when one wish a precise evaluation from the phenomenon. Outcomes also show that the boundary element method is an important technique for analyzing cereal grain drying behavior by diffusion equation due its precision, stability and computers processing facilities.